Minat Beli Konsumen terhadap Suasana Toko dan Lokasi - Hayani Hayani (Journal of Management and Bussines (JOMB), 2021)
This study aimed to determine the effect of store atmosphere and location on consumer buying interest at the Rabbani Bandar Agung Lahat outlet. The sampling technique used in this study is incidental sampling. Then the analysis was carried out using the T test, and the F test. The results showed that the regression equation obtained was: Y=3.879 +0.514 X_1 +0.687 X_(2 )+e. Store atmosphere variable with t count > from t table or 2,537 > 1,960, and location variable with t count > from t table or 3,497 > 1,960. The calculated F value is 126,504, so the calculated F value > F table. The conclusion is that there is a significant influence between the store atmosphere variable, the location variable, and both of them together on the consumer buying interest variable. Keywords: Location, Consumer Buying Interest, Store Atmosphere